Digitalization of Promotions in an Effort to Increase Sales of Hijab Products at the Yumeoursyle Online Store on the TikTok Shop Marketplace - Reni Nuraeni; Tiris Sudartono (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Indonesia, as the country with the largest Muslim population, has experienced rapid growth in the Muslim fashion industry, particularly in hijabs, which have now become part of the fashion trend among Muslim women in Indonesia. This change in perception provides opportunities for business actors to expand their ventures. The aim of this study is to examine how the digitalization of promotion affects the increase in hijab product sales at the Yumeourstyle store, which uses the Tiktok Shop platform. Using a descriptive qualitative method, there are four elements of the marketing mix: product, price, place, and promotion, which impact sales. The findings show that although Yumeourstyle has implemented digitalization in the form of sales through Tiktok Shop, the digital promotion is still not maximized. Promotion through live streaming, endorsement ads, and more engaging and consistent video content management need to be improved to increase consumer engagement and boost sales. Recommendations include enhancing promotion through celebrity endorsements, conducting more regular live streaming, and uploading video content consistently to expand market reach and increase sales.